Administrative Theories and Politics - SELF, Peter (George Allen & Unwin, 1979)
Allen & Unwin, 1972. Paperback. Condition: Very Good. Administrative Theories and Politics: An Enquiry into the Structure and Processes of Modern Government This book is in very good condition and will be shipped within 24 hours of ordering. The cover may have some limited signs of wear but the pages are clean, intact and the spine remains undamaged. This book has clearly been well maintained and looked after thus far. Money back guarantee if you are not satisfied. See all our books here, order more than 1 book and get discounted shipping. . Seller Inventory # 7719-9780043510438